Motivational Interviewing to Support Oral AntiCoagulation adherence in patients with non-valvular Atrial Fibrillation (MISOAC-AF): a randomized clinical trial. Issue Volume 7:Issue FI1(2021) (27th April 2020) - Tzikas, Apostolos; Samaras, Athanasios; Kartas, Anastasios; Vasdeki, Dimitra; Fotos, George; Dividis, George; Paschou, Eleni; Forozidou, Evropi; Tsoukra, Paraskevi; Kotsi, Eleni; Goulas, Ioannis; Karvounis, Haralambos; et al.
Abstract: Aims: We aimed to assess the impact of an educational, motivational intervention on the adherence to oral anticoagulation (OAC) in patients with non-valvular atrial fibrillation (AF). Methods and results: Hospitalized patients with non-valvular AF who received OAC were randomly assigned to usual medical care or a proactive intervention, comprising motivational interviewing, and tailored counselling on medication adherence. The primary study outcome was adherence to OAC at 1 year, which was evaluated according to proportion of days covered (PDC) by OAC regimens and was assessed through nationwide registers of prescription claims. Secondary outcomes included the rate of persistence to OAC, gaps in treatment, and clinical events. A total of 1009 patients were randomized, 500 in the intervention group and 509 in the control group. At 1-year follow-up, 77.2% (386/500) of patients in the intervention group were adherent (PDC > 80%), compared with 55% (280/509) in the control group [adjusted odds ratio (aOR) 2.84, 95% confidence interval (CI) 2.14–3.75; P  < 0.001]. Mean PDC ± standard deviation was 0.85 ± 0.26 and 0.75 ± 0.31, respectively ( P  < 0.001). Patients that received the intervention were more likely to persist in their OAC therapy at 1 year (aOR 2.42, 95% CI 1.71–3.41; P  < 0.001). Usual medical care was associated with more major (≥3 months) treatment gaps (aOR 2.39, 95% CI 1.76–3.26; P  < 0.001). Clinical events over a median follow-up period of 2 years did not differ among treatment groups. Conclusion: In patients receiving OAC therapy for non-valvular AF, a multilevel motivational intervention significantly improved medication adherence and rate of therapy persistence, and reduced major gaps in treatment. No significant impact on clinical outcomes was observed. Trial registration number: NCT02941978.